On The Stability for Covid-19 Model - Jwan S. Ali; Hero W. Salih (ASJ - Academic Science Journal, 2024)
In this paper, we investigate the stability of an impulsive mathematical model for a biologicalphenomenon that caused millions of people to die in these recent years, and it is thephenomenon of the COVID-19 epidemic, which first appeared in Wuhan, China. In this studywe are working on the system that was proposed by Ndaïrou et al [1] to define the dynamics ofCOVID-19 model. For the stabilization study we use the direct and indirect Lyapunov method.Before we start a study, we must find all the critical points of the system. For more study, weperturbation the system by adding very small positive quantities, because in finding criticalpoints we have three free variables in case of perturbation, can work on more points. Itphysically means that we can control a patient's condition and reduce the number of dead andinjured recovering.